Statistical modelling of extreme rainfall, return periods and associated hazards in the Bamenda Mountain, NW Cameroon = Modelação estatística e tempos de retorno de precipitações extremas associadas a desastres naturais na serra de Bamenda, NW dos Camarões - Afungang, Roland Ngwatung (2016)
The Bamenda mountain region has one of the highest frequencies of landslides in Cameroonand the lowlands are prone to floods. The occurrence of these hazards is attributed to theestimated 2500 mm of rainfall that the area receives annually. The aim of this paper was toestimate the maximum rainfall the area is likely to receive in future and to examine somepast extreme rainfall episodes that triggered landslides and floods and their return periods.The type I extreme value (Gumble) distribution was used to make these estimates throughan Excel worksheet. From the model, it was predicted that the area could receive amaximum rainfall of about 87.7mm/day in 3 years, 116.97mm/day in 25 years,126.13mm/day in 50 years and 135.23/day in 100 year. Seven extreme rainfall episodeswere identified within the 43 year study period with rainfall amounts ranging from99.5mm/day to 129.3mm/day. The extreme rainfall episodes initiated both landslide andfloods and with return periods ranging between 7.3 years to 68.9 years. Predicting theseextreme cases can be useful in the construction of dams and bridges and further researchon rainfall thresholds for rainfall-induced hazards affecting the region.